Coastal ocean observing systems - Liu, Yonggang; Kerkering, Heather; Weisberg, Robert H. (Elsevier, 2015)
Coastal Ocean Observing Systems provides state-of-the-art scientific and technological knowledge in coastal ocean observing systems, along with guidance on establishing, restructuring, and improving similar systems. The book is intended to help oceanographers understand, identify, and recognize how oceanographic research feeds into the various designs of ocean observing systems. In addition, readers will learn how ocean observing systems are defined and how each system operates in relation to its geographical, environmental, and political region. The book provides further insights into all of these problem areas, offering lessons learned and results from the types of research sponsored and utilized by ocean observing systems and the types of research design and experiments conducted by professionals specializing in ocean research and affiliated with observing systems.--Provided by publisher.